Influence of cleavage-stage embryo quality on the in-vitro fertilization outcome after single embryo transfer in fresh cycles - Yu Sun; Enshu Li; Guofang Feng; Miao Li; Yanling Fu; Jiali You; Xiaozhen Liu; Yimin Zhu (Elsevier, 2020)
Objective: Embryo quality is crucial for determining the outcome of embryo implantation. This study aimed to assess the impact of embryo quality on the outcome of in vitro fertilization/single-embryo transfer (IVF-SET). Materials and methods: This retrospective study included 2531 fresh IVF-SET cycles, including 277 poor-quality and 2254 top-quality embryos. The clinical pregnancy rate, miscarriage rate, live birth, implantation rate, pregnancy outcome and complication were analyzed and compared. Risk factors associated with miscarriage rate and pregnancy complication were identified using logistics regression analysis. Results: Top-quality embryos resulted in higher clinical pregnancy rate (30.5% vs. 12.6%, P < 0.001) and live birth rate (23.9% vs. 9.7%, P < 0.001) compared with poor-quality embryos. Logistics regression analysis revealed that embryo quality was not correlated with miscarriage rate (95% CI 0.33-1.89) and pregnancy complications (95% CI 0.12-7.84). Maternal age and body mass index was a risk factor for miscarriage rate (95% CI 1.05-1.22) and pregnancy complication (95% CI 1.01-1.29), respectively. Conclusion: Clinical miscarriage rate and pregnancy complication were embryo quality independent. Maternal age was the risk factor for miscarriage rate. Embryo quality did not affect miscarriage once a clinical pregnancy is achieved.